The short and one-year outcome of transcatheter Patent Ductus Arteriosus closure at Inkosi Albert Luthuli Central Hospital, Durban, South Africa: A Descriptive retrospective chart review - Koolash, K.; Hoosen, E.G.M. (SA Heart Journal, 2020)
Background: Transcatheter closure of patent ductus arteriosus is a common intervention worldwide. A review of the outcomes of patients undergoing this procedure was undertaken at a central hospital in Durban, South Africa. Methods: Retrospective observational descriptive study of the short (<1 year) and long-term (>1 year) efficacy and safety of patients who underwent transcatheter closure of PDA from January 2010 - December 2015 at Inkosi Albert Luthuli Central Hospital (IALCH), Durban, KwaZulu-Natal. Results: Over the 5 years, 181 patients underwent cardiac catheterisation for PDA closure: 170 (93.9%) had successful percutaneous closure, and 11 (6.07%) required surgical ligation. Mean age was 30.2 ± 9.7 months, weight 11.2kg ± 3.6kg, PDA diameter on echocardiography was 3.64mm (SD ± 0.97mm), fluoroscopy time 13.66 minutes (SD ± 4.37min) and radiation dose 468.61 microGrays (SD ± 149.9microGrays). Devices used included the Amplatzer Duct Occluder (ADO) I, ADO II, ADO II AS, Cera, Occlutech, detachable coils and vascular plugs. Twenty-five patients (15%) had complications (6 major: 2 device embolisation, 1 blood loss and 3 pulse loss). Conclusion: Percutaneous PDA closure at IALCH, South Africa, had a comparable level of safety and efficacy to reports from other centres.